If it's not what You are looking for type in the equation solver your own equation and let us solve it.
29x+19=17
We move all terms to the left:
29x+19-(17)=0
We add all the numbers together, and all the variables
29x+2=0
We move all terms containing x to the left, all other terms to the right
29x=-2
x=-2/29
x=-2/29
| ½x=-½x+4 | | 35-18=x | | 9n-45+8n+32=2 | | 5x+1+3x-7=90 | | 4t-3(t+6)=t+6 | | 1.88g-4=0.70 | | 7/6x=56 | | -2(x+4)-9=14-x | | 2(x-3)^3-8(x-3)^2=0 | | -19-7x=-6(x+4) | | 6x-(3x+15)=3 | | b-5+6b=33 | | 15=4x+1-2x | | 13+2x=x+20 | | 3.9=7.4-0.5x | | 0.6(k-3)=0.4k+5.6-0.5-0.1 | | 3(x+2)2−189=0 | | 6(x-5)^4+4(x-5)^2=0 | | 16t-19t=18 | | (6-u)(3u+7)=0 | | 27.4x=33.68 | | 9=19+a | | b–3(3–4b)=7 | | 4x-48=-7x+12 | | 26x+20=25x+15 | | √8^x-2=0 | | 250/95=x/75 | | -7x-8=10x+4 | | 9-5x=-6x+3 | | 49-y=233 | | (5x+9)=2(2x-3) | | Y=1200+12x |